Penetapan Tarif Pajak Penghasilan Dalam Transaksi Jual Beli E-Commerce - Lesiyela, Absa Brian; Tita, Heillen Martha Yosephine (CAPITAN: Constitutional Law & Administrative Law Review, 2024)
Income tax rates need to be regulated in an appropriate regulation in order to emphasize the imposition of income tax on those who carry out e-commerce buying and selling transactions, so that income tax is imposed fairly. So, levying income tax on e-commerce buying and selling transactions is the state's obligation to impose it on entrepreneurs who carry out e-commerce buying and selling transactions. The type of research that will be carried out in this writing is legal research with a normative juridical or analytical descriptive approach. Normative legal research is a type of legal research that involves an internal perspective with a focus on legal norms as the research object. When e-commerce tax collection rules are also applied to e-commerce buying and selling transactions, there will be no social inequality or movement of entrepreneurs in the e-commerce sector. Based on Minister of Finance Regulation Number 210 of 2018, the obligation to treat income tax like conventional traders is not mentioned at all. This regulation has caused problems and rejection from the Indonesian e-commerce association (idea) because it does not create a level playing field/fairness.